IDENTIFICATION OF POTENTIAL SITES FOR HOOP PINE PLANTATIONS IN THE ATHERTON TABLELANDS, NORTH QUEENSLAND, USING GIS AND EXPERT KNOWLEDGE - Ike Sari Astuti (Universitas Negeri Malang, 2011)
Abstract: This study modeled the suitability of sites to establish hoop pine plantations in the Atherton Tablelands, North Queensland (NQ). The study was conducted to provide information regarding potential sites resulted from a broad level site assessment. Potential sites for hoop pine were identified using GIS which the criteria were derived from literature search and expert opinion which then were used to construct suitability criteria. Mean annual rainfall and soil types were used to assess the ecological suitability for hoop pine growth. These suitabilitycriteria were then combined with availability criteria for determining possible expansions of hoop pine plantations on private lands, which comprise the land size, land status, land cover, land use and slope limit. The model was then validated using hoop pine site index records as a surrogate for hoop pine potential growth. From the results, the region was found to be edaphically and climatically suitable encompassing around 35,567 ha of land was identified as highly suitable and 4,680 ha as moderately suitable. It was also revealed that suitability classes derived from spatial modeling can only produce indicative locations of lands suitable for supporting hoop pine growth. While datasets came from various scales and precision, the results of the study have limited applicability for planning at individual farm but are useful to gain initial consideration at the regional level to target areas for plantation expansion.Keywords: Hoop pine, land suitability, land-availability, GISbased modeling